Last layer : new methods in digital printing for photography, fine art, and mixed media - Lhotka, Bonny Pierce (Voices that matter., 2013)
In The Last Layer–the follow-up to Digital Alchemy, her successful book on alternative printmaking techniques–Bonny Lhotka teaches how to make prints that take their inspiration from early printmaking processes. In this book, Lhotka shows readers step-by-step how to create modern-day versions of anthotypes, cyanotypes, tintypes, and daguerreotypes as well as platinum and carbon prints. She also reinvents the photogravure and Polaroid transfer processes and explores and explains groundbreaking techniques for combining digital images with traditional monotype, collograph, and etching press prints. By applying these classic techniques to modern images, readers will be able to recreate the look of historical printmaking techniques and explore the limits of their creative voice. Best of all, the only equipment required is a desktop inkjet printer that uses pigment inks, and a handful of readily available materials and supplies–not the toxic chemicals once required to perform these very same processes. Leveraging her training as a traditional painter and printmaker, Bonny Lhotka brings new innovations and inventions that combine the best of centuries of printmaking technique with modern technology to create unique works of art and photography. After years of experimentation and development, these new processes allow alternative photographers, traditional printer makers, and 21st century digital artists to express their creative voice in ways never before possible.